Teaching Spanish to Migrants: Meanings Constructed by University Students on the Pedagogical Interaction in the Classroom [Enseñanza de Español Para Migrantes: Significados Construidos por Estudiantes Universitarios Sobre la Interacción Pedagógica en el Aula] - Rubio-Manriquez, M; Rubio-Martin, R (Universidad de la Serena,Departamento de Artes y Letras, 2021)
This article aims to describe the meanings that a group of university students constructed on the experience of teaching Spanish to Haitian migrants. The methodology corresponds to a qualitative case study. The case is an university social responsibility project managed by academics from the University of Santiago de Chile, who train, guide and accompany a group of university students in their work as monitors. The sample consisted of 9 students (monitors), with one year of experience in the project, divided into two conversation groups. The analysis process was inductive in nature. Results indicate that the monitors experienced a process of adjustment of expectations concerning the teaching of a language, the emerging situations, their degree of autonomy, the didactic interaction, the learners, and their own abilities as teachers, among others. It is concluded that the intervention model based on learning by doing and cooperative learning is valid for the training of specialists in Spanish as a Foreign Language (SFL) teaching, although it is necessary to rethink the process of classroom supervision by the academics in charge of the project. © 2021 Universidad de la Serena,Departamento de Artes y Letras. All rights reserved.